Use of Chinese medicine by cancer patients: a review of surveys - Smith Caroline A; Carmady Bridget (BMC, 2011)
Abstract Chinese medicine has been used to treat a variety of cancer-related conditions. This study aims to examine the prevalence and patterns of Chinese medicine usage by cancer patients. We reviewed articles written in English and found only the Chinese medicine usage from the studies on complementary and alternative medicine (CAM). Seventy four (74) out of 81 articles reported rates of CAM usage ranging from 2.6 to 100%. Acupuncture was reported in 71 out of 81 studies. Other less commonly reported modalities included Qigong (n = 17), Chinese herbal medicine (n = 11), Taichi (n = 10), acupressure (n = 6), moxibustion (n = 2), Chinese dietary therapy (n = 1), Chinese massage (n = 1), cupping (n = 1) and other Chinese medicine modalities (n = 19). This review also found important limitations of the English language articles on CAM usage in cancer patients. Our results show that Chinese medicine, in particular Chinese herbal medicine, is commonly used by cancer patients. Further research is warranted to include studies not written in English.